Estimation of Additive, Non Additive Gene Effects and Genetic Parameters on Pre-Weaning Growth Traits in Goats Meat in Southern Thailand - SUPAKORN, China; PRALOMKARN, Winai; TUMWASORN, Sornthep (Walailak Journal of Science and Technology (WJST), 2011)
A total of 791 animals involved in Thai Native (T), Boer (B), Saanen (S) and their crosses were studied. Fixed effects of sex, birth type, breed group and year-season of birth were found to significantly affect birth weight (BW), weaning weight (WW) and average daily gain (ADG) (P < 0.05). Two statistical models were analyzed in this study. The first model showed that the B breed had higher BW and the S breed had highest WW and ADG than the others (P < 0.05). The T breed had the lowest BW, WW and ADG (P < 0.05) among all breeds and breed crosses. Direct additive and maternal breed effects of B and S breeds from Model 2 had significantly positive values (P < 0.05). It indicated that the B and S purebreds had heavier body weights than the T breed. Direct heterosis, maternal heterosis and recombination effects were not significant. The heterosis estimates of crossbreeding between S and T purebreds tended to yield heavier weaned kids (P > 0.05). Estimated direct and maternal heritabilities were found to be 0.25 and 0.08 for BW, 0.38 and 0.11 for WW and 0.35 and 0.12 for ADG. The direct genetic, maternal genetic and phenotypic correlations among pre-weaning traits were positive with moderate to high values (0.30 to 0.89). The findings provided basic information that farmers and breeders could utilize for an appropriate approach to crossbreeding and monitoring the genetic potential in this herd.